Cytoskeleton changes of mammalian cells in microgravity: results from three decades of low-gravity research - Wuest, Simon L. (Frontiers in Space Technologies, 2025)
With the onset of human space flight, the profound consequences of microgravity (or weightlessness) on living organisms became apparent. Subsequently, understanding the biological processes and developing effective countermeasures has moved into the research focus. Despite their small size, isolated cells also show many adaptations in microgravity, but many fundamental processes are not understood. Because the cytoskeleton largely determines cells’ mechanical properties and is thought to play an important role in cellular mechanosensing, cytoskeleton adaptation in microgravity have been the focus of many research studies. More than 35 years ago, microtubules assembled in a cell-free system were demonstrated to be gravity dependent. Since then, multiple studies have described cytoskeleton adaptations in varieties of cells exposed to short- or long-term microgravity. In this paper on cytoskeletons in microgravity research, I aimed to grasp the published results as a bigger picture and quantify the reported effects in a systematic and more objective manner. The paper focuses on mammalian cells exposed to real microgravity (free fall) and starts with a brief review on the mechanisms how cells can or could sense their physical environment and the role of the cytoskeleton in mechanobiology.